Revealing Postgraduate Students' Experiences of Using Artificial Intelligence (AI) for Academic Purposes - Lazuwardiyyah, Fairuz; Setiawan, Slamet; Widyastuti; Mustofa, Ali (Institut Agama Islam Negeri Palopo, 2025)
The increasing usage of artificial intelligence technology has resulted in an increasing variety of uses in the area of education, especially language learning. This research aims to investigate postgraduate students' experiences when using AI for academic purposes. The study reveals that postgraduate students use AI for academic purposes, including interpreting complex vocabulary and verifying their translations. In addition, this research showed that they have cognitive, affective, and behavioral attitudes toward AI but also express concerns about cheating, grammatical errors, and dependency. Furthermore, postgraduate students vocalized the quality of their translations to machines, stating they were similar but had grammatical errors and were relevant to the topic but sometimes not appropriate with the context.